Expression of functional toll like receptor 4 in estrogen receptor/progesterone receptor-negative breast cancer. Issue 1 (December 2015) - Mehmeti, Meliha; Allaoui, Roni; Bergenfelz, Caroline; Saal, Lao; Ethier, Stephen; Johansson, Martin; Jirström, Karin; Leandersson, Karin
Abstract Introduction Toll-like receptors (TLRs) are a family of pattern recognition receptors that are expressed on cells of the innate immune system. The ligands can be pathogen derived (pathogen associated molecular patterns; PAMPs) or endogenous (damage associated molecular patters; DAMPs) that when bound induces activation of nuclear factor kappa B (NF-κB) and transcription of pro-inflammatory genes. TLRs have also been discovered in various malignant cell types, but with unknown function. Methods In this study we performed a detailed analysis of TLR and co-receptor expression pattern and function in breast cancer. Expression patterns were examined using real-time quantitative polymerase chain reaction (RT-qPCR) and immunohistochemistry (IHC) on three estrogen receptor-positive (ER+ ) and four estrogen receptor/progesterone receptor-negative (ER− /PR− ; ER/PR-negative) breast cancer cell lines, and a breast cancer cohort consisting of 144 primary breast cancer samples. The function was investigated usingin vitro assays comprising PAMP/DAMP-stimulation, downstream signaling and TLR-silencing experiments. Results We found that TLR4 was expressed in a biologically active form and responded to both PAMPs and DAMPs primarily in ER/PR-negative breast cancers. Stimulation of TLR2/4in vitro induced expression of pro-inflammatory genes and a gene expression analysis of primary breast cancers showed a strong correlation between TLR4 expression and expression of pro-inflammatory mediators. In line with this, TLR4 protein expression correlated with a decreased survival. Conclusions These findings suggest that TLR4 is expressed in a functional form in ER/PR-negative breast cancers. Studies regarding TLR4-antagonist therapies should be focusing on ER/PR-negative breast cancer particularly.